Role of public administration in optimization of interrelation of urban transport complex and logistics services - Yesenova, M.T.; Bugubaeva, R.O. (BUKETOV BUSINESS REVIEW, 2024)
Purpose: The main objective of the study is to analyze the relationship between urban transport and logistics ser vices in the Republic of Kazakhstan in order to identify key factors affecting their efficiency and interaction, and to develop recommendations for optimizing and improving the integration of these two components in the urban infra structure system. Originality: The study highlights the role of public administration in optimizing the relationship between urban transport and logistics services. This aspect of the study provides a deeper understanding of the mechanisms of the im pact of public policies on the operation and development of transport and logistics infrastructure in cities, necessary to develop practical recommendations and improve the interaction between urban transport and logistics services by ana lyzing the role of public administration. Results: The study analyzed the current state of transport and logistics systems, highlighted the main problems and potential opportunities for the creation of a more efficient, sustainable and coordinated infrastructure, contributing to the improvement of the quality of life of citizens and the development of the economy of the region. Conclusions: Improving the relationship between urban transport complex and logistics services in the Republic of Kazakhstan is an important step towards sustainable development of the country, creating favorable conditions for its citizens and ensuring economic growth. The author made a forecast for 2023–2025, using correlation and regression analysis, which shows that it is necessary to revise the policy regarding the system of state management of urban trans portation, as well as to develop recommendations to improve the management of urban logistics.